Adolescents' Attitude Towards Premarital Sex - Violla Anggiani; Taty Hernawaty; Efri Widianti (Universitas Muhammadiyah Semarang, 2020)
Pangandaran is a tourism place given more impact on behavior sexuality among adolescents. One of the factors that most influence this behavior is attitude. The attitude becomes a stimulus for adolescents in reflecting premarital sexual behavior. This research aimed to find out the adolescent's attitudes towards premarital sexual behavior in SMA X Pangandaran. This research used a descriptive quantitative method with a cross-sectional approach. The study population was adolescents at SMA X Pangandaran with a total of 842 people. The data collection used proportionate stratified random sampling, with the sample counted as 240 students. Data were collected within 2 weeks using BSAS which was distributed online and the validity test was carried out with a score of 0.896 and a reliability test with an Alpha value of 0.861. Data were analyzed by the mean and standard deviation formulas. In this study, adolescent attitudes toward premarital sexual behavior tend to be less accepting about sex (permissiveness) 43,40 ± 5,772, responsible for birth control 11,14 ± 2,820, do not tend to fuse with sex partners (communion) 14, 96 ± 4.892, and do not tend sexual orientation (instrumentality) 18.36 ± 4.007. The majority of students consider premarital sex is not allowed and is a taboo subject to talk about.